GERAKAN LITERASI PEDAGOGIK BAGI GURU UNTUK PENINGKATAN MUTU PEMBELAJARAN DI SDN DURI KEPA 17 PAGI DAN SDN JELAMBAR BARU 01 PAGI - Susanto, Ratnawati; Febrianti, Nurul; Husna, Nia Iftahul; Putri, Astri Anggita; Umri, Cut Alfina; Ramadhanti, Dita; Dwiyanti, Karina (Universitas Esa Unggul, 2018)
AbstractSDN Duri Kepa 17 Pagi and SDN Jelambar 01 Pagi have problems over pedagogic competency values that focus on the ability to understand the characteristics of the students. This is due to the absence of pedagogic pedagogy development programs for teachers after graduating from lectures and the challenges and developments of the era that influenced learning styles and educational interactions. So the solution offered is the accompaniment of Pedagogic Literacy Movement for the characteristics of learners. Method of implementation of socialization, training, self-evaluation, reflective pedagogical paradigm, exploration, simulation, documentation, discussion of friendship, mapping and practice. Objectives Outcome targets: (a) Training and advisory services of knowledge up to the formation of pedagogic competence, (b) Products: Modules, Worksheets, PPR matrices, Journal of Friendship, Matrix Johari Window and TSM, (c) HaKI, (d) Journal of Abdimas Esa Unggul University and additional procedural of SNIPMD, (e) Publication on Esa Superior University repository. The result obtained is an increase in pedagogic literacy. The conclusion is that there are improvements: (a) School paradigm as a learning organization, (b) pedagogic theory knowledge, (c) variation of teaching approach, (d) variation of teaching style, (e) communication model, (f). Ability to identify the characteristics of students, (g) attitude of entry behavior.Ã‚Â Keywords: school literacy movement, pedagogic literacy movement, quality of learningÃ‚Â AbstrakÃ‚Â SDN Duri Kepa 17 Pagi dan SDN Jelambar 01 Pagi memiliki permasalahan atas nilai-nilai kompetensi pedagogik yang berfokus pada kemampuan memahami karakteristik anak didik. Hal ini disebabkan karena tidak terdapatnya program pengembangan kompetensi pedagogik bagi guru setelah lulus dari perkuliahan dan berbagai tantangan dan perkembangan era yang berpengaruh pada gaya belajar dan interaksi edukatif. Maka solusi yang ditawarkan adalah pendampingan Gerakan Literasi Pedagogik untuk karakteristik peserta didik. Metode pelaksanaan sosialisasi, pelatihan, evaluasi diri, paradigma pedagogik reflektif, eksplorasi, simulasi, dokumentasi, diskusi pertemanan, pemetaan dan praktek. Tujuan Target luaran: (a) Jasa pelatihan dan pendampingan pengetahuan hingga kepada terbentuknya kompetensi pedagogik, (b) Produk : Modul, Lembar kerja, matriks PPR, Jurnal Pertemanan, Matrikx Johari Window dan TSM, (c) HaKI, (d) Publikasi pada Jurnal Abdimas Universitas Esa Unggul dan tambahan proceding SNIPMD, (e) Publikasi pada repository Universitas Esa Unggul. Hasil yang diperoleh adalah peningkatan literasi pedagogik. Kesimpulannya adalah terdapatnya peningkatan: (a) Paradigma sekolah sebagai organisasi pembelajaran, (b) pengetahuan teori pedagogik, (c) variasi pendekatan mengajar, (d) variasi gaya mengajar, (e) model komunikasi, (f). Kemampuan mengidentifikasi karakteristik anak didik, (g) sikap melakukan entry behavior.Ã‚Â Kata kunci: gerakan literasi sekolah, gerakan literasi pedagogik, mutu pembelajaran